SISTEM INFORMASI PENGGAJIAN KARYAWAN MINIMARKET DI SPBU PONDOK PESANTREN SALAFIYAH SYAFI’IYAH - Wilda Aluf (Jurnal Ilmiah Informatika, 2019)
The development of technology information and communication has a positive impact in the way of accessible information as we need. Companies should apply this information system in their activities to win the competition. One of the parts to which the system information is considered applicable is in the system of remuneration. Though the implementation of remuneration information system, it is expected to enable to handle the remuneration transaction in the way that it can run well and be done in minimal errors. This research aims at developing a remuneration information system that includes data processing of the employee’s salary and the report. The tools that are used to perform the analysis and the design is Data Flow Diagram (DFD) while the programming language used to design the system is PHP and MySQL. The result of this research is a computerized remuneration information system that can be used to conclude that the proposed system can effectively meet what the management of a company wants.